2011
DOI: 10.1038/nphys1940
|View full text |Cite
|
Sign up to set email alerts
|

Probing collective multi-electron dynamics in xenon with high-harmonic spectroscopy

Abstract: High-harmonic spectroscopy provides a unique insight into the electronic structure of atoms and molecules 1-5. Although attosecond science holds the promise of accessing the timescale of electron-electron interactions, until now, their signature has not been seen in high-harmonic spectroscopy. We have recorded high-harmonic spectra of atoms to beyond 160 eV, using a new, almost ideal laser source with a wavelength of 1.8 µm and a pulse duration of less than two optical cycles. We show that we can relate these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
340
4
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(370 citation statements)
references
References 28 publications
14
340
4
2
Order By: Relevance
“…The last step, photorecombination, is now well understood in terms of quantum scattering calculations developed in the context of photoionization. [15,16,19] Most remarkably, the strong laser field does not lead to a measurable distortion of the electronic wave functions within the accuracy of current experiments, even in polarizable systems like xenon [20] or in molecules with appreciable extension along the direction of the laser field like CO 2 . [4,5] The second step, propagation of the electron wavepacket, is largely dominated by the laser field and is well described by classical equations as evidenced by, e.g.…”
Section: Probing Chemical Reactionsmentioning
confidence: 59%
“…The last step, photorecombination, is now well understood in terms of quantum scattering calculations developed in the context of photoionization. [15,16,19] Most remarkably, the strong laser field does not lead to a measurable distortion of the electronic wave functions within the accuracy of current experiments, even in polarizable systems like xenon [20] or in molecules with appreciable extension along the direction of the laser field like CO 2 . [4,5] The second step, propagation of the electron wavepacket, is largely dominated by the laser field and is well described by classical equations as evidenced by, e.g.…”
Section: Probing Chemical Reactionsmentioning
confidence: 59%
“…1.2.1), the electronic structure of molecular orbitals, or electronelectron interaction is imprinted on the HHG spectrum. In a recent experiment Shiner et al [21] recorded high-harmonic spectra of several atoms (Kr, Xe and Ar) for the photon energy up to 160 eV using a few-cycle 1.8-µm laser. They showed that these spectra can be related to differential photoionization cross sections measured with synchrotron sources, and these spectra contain features due to collective multi-electron effects involving inner-shell electrons, in particular the giant resonance in Xe.…”
Section: Probing Electronic Structure and Dynamics Of Atoms And Molecmentioning
confidence: 99%
“…Their interpretation is often based on the idea that the frequencydomain HHG yield can be factorized in terms of an electron wave packet (EWP) that depends on the parameters of the strong laser field driving the harmonic emission and the (field-free) photorecombination cross section (PRCS) of the atomic or molecular target [3]. This assumption has been successfully used to retrieve the PRCS (or, equivalently, the photoionization cross section, which can be related to the PRCS using the principle of detailed balance) from measured HHG spectra (see, e.g., [2]). For a linearly polarized field, this factorization was proposed phenomenologically, based on numerical solutions of the time-dependent Schrödinger equation [3,4].…”
mentioning
confidence: 99%
“…In addition to its important technological applications, such as the production of attosecond pulses, high-order harmonic generation (HHG) is now widely used in spectroscopic applications, allowing one to image atomic and molecular dynamics [1,2]. Most experiments on HHG spectroscopy have been performed with a linearly polarized laser field.…”
mentioning
confidence: 99%
See 1 more Smart Citation